The contribution of perceptual-cognitive skills to reactive agility in early and middle adolescent soccer players - Horníková, H.; Hadža, R.; Zemková, E. (The Journal of Strength and Conditioning Research, 2025)
Agility performance increased from childhood to mid-adolescence, followed by a plateau until early adulthood. Because adolescence is crucial for the development of perceptual-cognitive skills, the question is whether and to what extent its contribution to reactive agility increases during developmental periods of adolescence in invasive sports athletes. This study investigated the association of reactive agility with the speed of decision making, sprint speed, and explosive strength in early and middle adolescent soccer players. They performed reactive and preplanned Y-shaped agility tests, choice reaction time test, modified half T-test, 30-m sprint (10 m split), and countermovement jump (CMJ). The reactive agility time in both age groups significantly correlated with 30-m sprint time (r = 0.839, p < 0.001, and r = 0.745, p = 0.001, respectively), pre-planned Y-shaped agility time (r = 0.828, p < 0.001, and r = 0.644, p = 0.007, respectively), 10-m sprint time (r = 0.823, p < 0.001, and r = 0.775, p < 0.001, respectively), time in modified half T-test (r = 0.723, p < 0.001, and r = 0.630, p = 0.009, respectively), and CMJ height (r = -0.744, p < 0.001, and r = -0.615, p = 0.013, respectively), although with the index of reactivity in middle adolescent soccer players only (r = 0.615, p = 0.011). Based on R^2, the explained proportion of variance was 53.6% for linear sprint speed and 30.1% for a change of direction speed in early adolescence, whereas it was 54.6% for acceleration speed and 31.8% for decision-making in middle adolescence. This indicates the significant contribution of speed factors to reactive agility in both adolescent groups, whereas perceptual-cognitive factors in middle adolescent soccer players only. It seems that even during the relatively short period of adolescence, the changes occur in the contribution of perceptual-cognitive skills to reactive agility in athletes practising invasive sports.